The Effectiveness of Acceptance and Commitment Therapy on Marital Tension and Forgiveness among Women Seeking Divorce - Zekariazadeh Khatir, Zeinabkhaton; fakhri, Mohammadkazem; haydari, shaban (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of acceptance and commitment-based treatment on marital tension and forgiveness among women seeking divorce in Babol. Methods: The present study was a quasi-experimental study with a two-group pretest-posttest design. Among the women seeking divorce, a sample of 30 people was selected by purposive non-random sampling method and replaced in a experimental group (acceptance and commitment therapy) and a control group by simple random sampling. (15 people in each group). After evaluating 30 women applicants for divorce, whose level of covert communication violence was higher than the cut-off point and had the necessary conditions, it was identified and then divided into three groups of 15, two experimental groups and one control group. Then, 8 sessions of 90-minute treatment based on acceptance and commitment (Hayes et al., 2004) were performed in the experimental group in person and in accordance with health protocols. Data were collected using the Stockholm Orth Gomer et al. (2000) Marital Stress Scale and the Pollard & Anderson (1988) Forgiveness Questionnaire. Data were analyzed using repeated measures analysis of variance. Results: The results showed that acceptance and commitment-based therapy on marital stress (F=31.53, p